PENGARUH VOLUME ISIAN DAN PANJANG PIPA FRAKSINASI TERHADAP KINERJA DESTILATOR BERTINGKAT - , AMIQ NURUL AZMI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Premium fossil fuel has nonrenewable characteristic, means it is prone to scarcity or even used up. Bioethanol is an alternative energy that is renewable, for it comes from biomass that contains carbohydrate. Indonesia has the potency to produce bioethanol, seen from the countryâs great quantities of biomass such as corn, buckwheat, cassava, sticky rice, etc. In order to obtain high percentage of bioethanol, a good distillation technology is important. This research aims to increase the work of distillation equipment to produce bioethanol as alternative fuel by setting the pipes with various additional lengths of 30cm, 60cm and 90 cm, and also various amount of iron fiber as filling of none, half and full. The work of staged distillatory is analyzed based on the observation on the capacity of the bioethanol result, distillate result percentage, optimum time of distillation, residue of bioethanol percentage from fractional pipe, and bioethanol pure volume per 1 kilogram of material. The research found that the highest capacity of bioethanol is 131,04 ml in 60 cm pipe with half filling, the highest distillate percentage is 73,33% in 90 cm pipe with full filling, the fastest distillation time is 73,33 minutes in 90 cm pipe with none filling, the lowest bioethanol residue is 0% in 30 cm pipe with none filling, and the highest volume per kilogram material is 108,91 ml/kg on 90 cm pipe with full filling. The best additional fractional pipe length and iron fiber filling is the 90cm length pipe and full filling.